DIVERSITY AND ABUNDANCE OF MITES IN A MANDARIN CITRUS ORCHARD IN WEST SUMATRA - ., Affandi; Corpuz-Raros, Leonila A. (Indonesian Journal of Agricultural Science, 2005)
Some of the most destructive pests in citrus orchards are spider mites.Â  Monitoring prior applied pest control is a standard procedure for integrated pest management (IPM). The study aimed to survey and determine the distribution, abundance, and diversity of phytophagous, predatory, and detritivorous mites at different stages of development of arboreal plant parts, weeds and litter in the citrus orchard. A periodical sampling surveymethod was conducted on six growth stages of mandarin citrus, weeds and litter of the Indonesian Fruits Research Institute experimental field in Solok, West Sumatra in December 2003 to June 2004. All mites attached on each growth stage of citrus, weeds and litter were trapped and mounted on slide for identification purposes. Identification of the mites was conducted in the Acarology Laboratory, Department of Entomology, University of the Philippines at Los Banos in July-October 2004. The results showed that a very rich mite fauna of 130 species was found in the arboreal parts of citrus crops, weeds and litter below the canopy of the citrus orchard. Among the trophic groups, detritivorous mites were the most abundant, followed by the predators, phytophages, and thoseunknown feeding habit. Among the habitats, weeds harbored the most mite species followed by litter and arboreal parts of the citrus trees. The flush growth stage had the least diverse mite fauna with index diversity (Hâ) of 1.27, while the most diverse (Hâ = 2.01) was found at fruit development phase II. Result of this research was useful in determining proper time for controlling phytophagous mites. Besides, the result alsoprovides important information on potential predatory mites that can be used as biological control agents. Furthermore, the study implies the importance of maintaining cover crops of weeds and litter beneath the citrus trees as refuge and source of alternate prey for predators which suppressed populations of phytophagous mites.